Serum cytokeratin 19 fragment 21‐1 and carcinoembryonic antigen combination assay as a biomarker of tumour progression and treatment response in extramammary Paget disease. (24th June 2019) - Nakamura, Y.; Tanese, K.; Hirai, I.; Amagai, M.; Kawakami, Y.; Funakoshi, T.
Summary: Background: Extramammary Paget disease (EMPD) is a rare intraepithelial adenocarcinoma affecting the genitals and axillary regions. As metastasis of these tumours is itself rare, solid disease management strategies have not been established. Serum carcinoembryonic antigen (CEA) and cytokeratin 19 fragment 21‐1 (CYFRA 21‐1) levels have been identified as candidate biomarkers for tumour progression in EMPD. Objectives: To determine the accuracy of and the correlation between these markers in patients with EMPD. Methods: Serum CEA and CYFRA 21‐1 levels were examined in 30 patients with EMPD treated at Keio University Hospital, and compared against clinical information. Both assays were performed at the time of diagnosis, during the postoperative observation period, and following systemic treatment in those with confirmed metastasis. Serum levels were then correlated with tumour progression status and treatment responses. Results: Normal levels for both assays were observed in all 11 patients with primary localized disease (100%). In patients with metastatic disease the CEA positivity rate was 79% (15 of 19 patients), with a rate of 63% (12 of 19 patients) for CYFRA 21‐1. Changes in CEA and CYFRA 21‐1 levels were statistically independent; however, using a combined view, elevated levels of either marker improved the positivity rate to 95% (18 of 19 patients). Use of both markers also correlated well with treatment responses. Conclusions: The combination of CEA and CYFRA 21‐1 is useful for predicting metastasis and treatment response in patients with EMPD, especially in those who only have elevation of a single marker. What's already known about this topic? Serum levels of carcinoembryonic antigen (CEA) and cytokine 19 fragment 21‐1 (CYFRA 21‐1) have been shown to be elevated in patients with extramammary Paget disease (EMPD). Elevation of serum CEA levels is associated with tumour progression of EMPD. A single small study reported that serum CYFRA 21‐1 levels are elevated in patients with EMPD with lymph node metastasis. What does this study add? Serum CEA and CYFRA 21‐1 were present in 79% and 63% of 19 cases of metastatic EMPD, respectively. Elevations of CEA and CYFRA 21‐1 were statistically independent. CEA and CYFRA 21‐1 combination assays were positive in 95% of cases of metastatic EMPD. What is the translational message? Combination assays with CEA and CYFRA 21‐1 are useful for monitoring treatment response in patients with metastatic EMPD, particularly in those with elevation of either marker. Abstract : Linked Comment : Ellis. Br J Dermatol 2019; 181 :439–440 . Plain language summary available online